Improving Mathematics Achievement and Self-Efficacy in Students with Mild Intellectual Disabilities using the 7Es Learning Strategy in Inclusive Classrooms in Calabar Education Zone of Cross River State, Nigeria - Ibok, Ekpenyong Effiong; Ogar, Raymond Ogbebe; Akpa, Stephen Ushie; Olofu, Paul Agbade; Obeten, Okoi Okorn; Ewa, James Abua; Obeten, Amos William; Unamba, Chioma Precious; Edeh, Stephen Olenye; Patrick, Elizabeth Odije; Bessong, Columbus Deku; Bessong, Napoleon Osang; et al. (Journal of Intellectual Disability - Diagnosis and Treatment, 2025)
Aim: The study examined the effect of the 7Es learning strategy on Mathematics achievement and self-efficacy of students with mild intellectual disabilities in an inclusive classroom in Calabar Education Zone of Cross River State, Nigeria. The study objectives were established to provide direction and focus for this research. Two research questions were formed, which were converted to two null hypotheses. A literature review was done based on the study variables, and the research gaps were also stated. Method: The study used a 2x2 factorial design in this investigation. The design was quasi-experimental and non-randomized. The population of the study consisted of 4,031 Senior Secondary (SSII) students with mild intellectual disabilities in Calabar Education Zone of Cross River State, Nigeria, of which a sample of 200 students with mild disabilities were selected (100 students were taught using the 7Es learning strategy, while 100 were taught using the traditional approach). The data was gathered using a mathematical achievement test (MAT) and a Mathematics Self-Efficacy Rating Scale questionnaire (MSERSQ). The reliability coefficients are strong (KR-20 = 0.88, Cronbach's Alpha = 0.90) for the MAT and MSERSQ, respectively, indicating good reliability. Two research hypotheses guided the study. Descriptive statistics were used to examine the data, and Analysis of Covariance (ANCOVA) was applied to test the null hypotheses. Results: The results of the analysis using ANCOVA indicated that students with mild intellectual disabilities who received tutoring using the 7Es learning strategy outperformed those who received tutoring using the traditional approach in terms of mathematics achievement (F-ratio = 268.399, p < 0.050), with a partial eta squared of 0.577 indicating a moderate effect, and self-efficacy (F-ratio = 1261.293, p < 0.050) with a partial eta squared of 0.865 indicating a high impact. Conclusion: The study concluded that the high academic achievement and self-efficacy of students with mild intellectual disabilities depend on the practical application of the 7Es teaching technique by teachers in teaching Mathematics concepts. Recommendation: Among other recommendations, the 7Es learning strategy should be adopted into the teaching and learning of Mathematics to improve mathematics achievement and self-efficacy of learners with diverse needs. Unique Contribution: This study's key contribution was to introduce the 7Es learning strategy as an effective pedagogical tool for enhancing mathematics achievement and self-efficacy of students with diverse needs.